Inoculating plant growth-promoting bacteria - effects on soil hydraulic properties and tomato root development under water stress conditions - Giovanna, Dragonetti; Soumiya, Cherradi; Francesca, Mapelli; Valentina, Riva; Redouane, Choukr-Allah; Oqbit, Weldeyohannes Amanuel; Sara, Borin (Agriculture and Food Sciences Research, 2024)
The plant growth promoting bacteria (PGPB) harbored in the rhizosphere develop specialized mechanisms that may have a key role to ameliorate soil properties and plant growth under prolonged dry conditions. Accordingly, this study aimed to assess the effects of bacterial growth on the soil hydraulic properties and the root response under water stress conditions induced by drip irrigated tomato. At pot scale, a silty soil was inoculated with two PGPB strains (Micrococcus yunnanensis M1 and Pseudomonas stutzeri SR7-77) to cultivate tomato plants under three different water regimes: full irrigation (100% of Pot Capacity- PC), moderate and severe water stress levels (75 and 50% of PC, respectively). Bacterized soil altered the pore size distribution of the rhizosphere compared to no-bacterized soil, increasing root zone plant-available water holding capacity. On the contrary, PGPB occupying the pores reduced the saturated hydraulic conductivity near-saturated soil conditions compared to the uninoculated trial. PGPB shown root surface density (RSD) equal to 0.540 % and 0.355 % to inoculated SR7-77 and M1 tests, respectively and under 50% PC, compared to 0.097% to the uninoculated soil test. Soil water potential values, retrieved through soil water retention parameters, were more negative to M1 and SR7-77 strains tests, corresponding to water hold in the pores with smaller radii conferring resistance to the plant following contrasting stresses. The results demonstrated that PGPB elongated continuous transmission pores and bridged with air-filled spaces in stressed periods.